POTENSI WISATA ALAM DI KESATUAN PENGELOLAAN HUTAN LINDUNG MODEL UNIT XIV TOBA SAMOSIR - Esra Barus; Rahmawaty Rahmawaty; Pindi Patana (Peronema Forestry Science Journal, 2016)
The region of  Unit XIV  Toba Samosir Forest Management Unit (KPHL Model Unit XIV Toba Samosir) has potential  ecotourism which are spreaded in several locations. The potential flora and fauna is one of the attractions of ecotourism in this region. This study aimed  to identify the potential of nature tourism in the area of KPHL Model Unit XIV Toba Samosir. The research was conducted from April to May 2015 use a survey method. There were five lines which can be develoved into an ecotourism region, they were Bukit Manja, Sampuran Jangga Dolok, Susur Sungai Lumbanjulu, Ekowisata Hutan Desa, Rumah Tarzan. Based on Eligibility  Value, KPHL Toba Samosir  ecotourism region deserves to be developed. The name of the track are bukit manja, sampuran jangga dolok, susur sungai lumbanjulu, ekowisata hutan desa, rumah tarzan.Keywords: Bukit Manja, Ecotourism, Forest Management Unit, Toba Samosir